QUALITY IMPROVEMENT IN CYLINDER BLOCK PRODUCTION: A SIX SIGMA APPROACH AT PT. XYZ - Rinawati, Dyah Ika; Sriyanto, Sriyanto (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2024)
The implementation of Six Sigma methodology has demonstrated significant effectiveness in enhancing quality and reducing defects in manufacturing processes. This study examines the application of Six Sigma principles to minimize defects in automotive cylinder block production. Employing the Define, Measure, Analyze, Improve, and Control (DMAIC) framework, the research identifies critical factors contributing to defects and implements strategic improvements to address quality issues. The Define phase established key elements related to quality products, including processes, suppliers, customers, and their requirements, utilizing SIPOC diagrams and Critical to Quality (CTQ) factors. In the Measure phase, data collection focused on determining process baselines and root causes, employing Defects Per Million Opportunities (DPMO) and Control Charts. Analysis revealed a DPMO value of 4,987 with a sigma level of 4.077σ. The Analyze phase identified causes of production process failures, with